EFL Instructional Materials Development Integrated with Playing Card Games and Islamic Perspectives (Conference on English Language Teaching, 2024)
This paper explores the intersection of Islamic views on EFL instructional material development and the integration of playing card games as a pedagogical tool for vocabulary teaching. The use of playing card games as a tangible and interactive resource in vocabulary teaching has been shown to enhance vocabulary retention, promote contextual understanding, and encourage active participation. By integrating playing card media as part of a comprehensive vocabulary instructional approach, individual learner needs can be considered, and various strategies can be incorporated to cater to different learning styles and proficiency levels. It becomes instructional techniques to address all language skills and components effectively. The combination of Islamic values, inclusive instructional materials, and interactive teaching approaches contributes to a holistic educational environment that promotes language proficiency, moral development, and intercultural understanding. This paper presents a qualitative library research methodology that aims at exploring Islamic perspectives on English as a Foreign Language (EFL) instructional material and communicative instruction through card games based on Islamic teachings. The result from this discussion is by upholding moral and ethical standards aligned with Islamic teachings, respecting cultural diversity, and using clear, accurate, and appropriate language, EFL instructional materials can be designed in a manner that aligns with Islamic values. Incorporating Islamic values and teachings within the instructional materials, where relevant, allows for a comprehensive approach that promotes not only language proficiency but also moral and character development in line with Islamic principles. Including elements of Islamic history and culture in the materials further promotes intercultural awareness among learners, fostering respect and understanding of different cultures.